Performance Enhancement In WDM – FSO System Using Semiconductor Optical Amplifier Under Different Rain Conditions - et. al., Ahmed Abdulelah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The free space optics (FSO) is considered as an attractive technology of telecommunication networks, due to several benefits as compared to other communication systems. However, signal degradation due to various weather conditions caused by wave attenuation can distort the performance of (FSO) connection link. The optimum performance is achieved by connecting a 5 Gbps optical amplifier at different places within the system. A laser source of 35 dBm power was transmitted at different weather conditions. Two systems were compared and analyzed. Results represented by both parameters (Q-factor, BER).